2020
DOI: 10.4025/actascianimsci.v42i1.50436
|View full text |Cite
|
Sign up to set email alerts
|

Protease and sugarcane yeast in diets for broiler chicks

Abstract: The objective of this study was to evaluate the inclusion of protease and sugarcane yeast in poultry diets on performance, organ weight, intestinal biometry, chemical composition and deposition of body nutrients in the 1 to 7-day old phase. The experimental design consisted of a randomized complete block design, in a factorial arrangement of 2 (without and with the enzyme protease) x3 (yeast levels: 0, 6 and 12%) +1 (positive control diet), totaling seven treatments with five replicates, birds per experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Several studies have shown that the use of proteases in poultry feed can increase body weight, feed conversion, and feed efficiency in broiler chickens, thereby reducing production costs and increasing productivity (Aaron J. Adeola, 2005;Lin Law et al, 2019;Moreira et al, 2020;Oxenboll et al, 2011;Pedersen et al, 2012;Philipps-Wiemann, 2018;L. F.;Romero & Plumstead, 2013).…”
Section: Effectiveness and Efficiency Of Enzymes In Poultry Feed Form...mentioning
confidence: 99%
“…Several studies have shown that the use of proteases in poultry feed can increase body weight, feed conversion, and feed efficiency in broiler chickens, thereby reducing production costs and increasing productivity (Aaron J. Adeola, 2005;Lin Law et al, 2019;Moreira et al, 2020;Oxenboll et al, 2011;Pedersen et al, 2012;Philipps-Wiemann, 2018;L. F.;Romero & Plumstead, 2013).…”
Section: Effectiveness and Efficiency Of Enzymes In Poultry Feed Form...mentioning
confidence: 99%